Implementation of Accrual-based Government Accounting in Local Government: Bourdieu's Habitus Theory - Rahayu, Hastanti Agustin (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p01, 2024)
The implementation of Government Regulation Number 71 of 2010 concerning Accrual-based Government Accounting Standards in order to improve the quality of financial reporting in realising accountable and transparent governance. This study aims to identify challenges in the process of implementing accrual-based accounting in the government environment. This research uses a descriptive qualitative approach with secondary data. The content analysis technique uses the habitus theory analysis knife by Pierre Bourdieu. The social actors in the implementation of accrual-based government accounting standards consist of the Governor, Regent, Deputy Regent and Mayor, KSAP and the Ministry of Home Affairs. According to Bourdieu's theory, the habitus is an obstacle in implementing accrual-based SAP where around fifty per cent of cases are based on the results of examination findings. Capital is social capital in the form of BPK RI audit results with an unqualified opinion. Arena is an accounting policy prepared by local governments based on guidelines set by the Ministry of Home Affairs. Keywords: SAP; Accrual; Bourdieu's Habitus Theory; Local Government